2015
DOI: 10.1093/ejcts/ezv228
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review comparing treatment outcomes of adjuvant lung resection for drug-resistant tuberculosis in patients with and without human immunodeficiency virus co-infection

Abstract: Lung resection for DR-TB may be safely undertaken in selected patients who are HIV-positive with cure rates equivalent to that of HIV-negative patients. More importantly, these patients also have significantly higher cure rates than those patients treated with medical therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…In a retrospective study of 14 XDR-TB patients and 36 MDR-TB cases undergoing surgical resection, Alexander and Biccard. 42 from South Africa concluded that lung resection for drug-resistant TB may be safely undertaken in selected patients who are HIV positive, with cure rates equivalent to HIV-negative patients, and that the patients treated surgically also have significantly higher cure rates than those treated with medical therapy alone.…”
Section: Drug-resistant Pulmonary Tuberculosismentioning
confidence: 99%
“…In a retrospective study of 14 XDR-TB patients and 36 MDR-TB cases undergoing surgical resection, Alexander and Biccard. 42 from South Africa concluded that lung resection for drug-resistant TB may be safely undertaken in selected patients who are HIV positive, with cure rates equivalent to HIV-negative patients, and that the patients treated surgically also have significantly higher cure rates than those treated with medical therapy alone.…”
Section: Drug-resistant Pulmonary Tuberculosismentioning
confidence: 99%
“…The outcomes of resectional surgery for MDRTB disease are summarized in ►Table 3, which depicts results from the Table 3 Case series, surgery for MDRTB/XDRTB 8,9,[11][12][13][14][33][34][35][36] n XDRTB (%) Morbidity (%) Mortality (%) Cure rate (%) (negative sputum) larger case series in the literature. 8,9,[11][12][13][14][33][34][35][36] In general, these operations, despite their complexity, may be performed with low morbidity and mortality. Some of the reported differences may be attributed to the varying patient populations, operations described, and health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of development of pleural tuberculosis remains to be elucidated. Based on currently available information, the mechanism underlying pleural tuberculosis is associated with these factors ( 7 , 9 11 ): i) Allergic effusion or immune defense disorders of organism and the gradual expansion of proliferation of mycobacterium tuberculosis or caseous lesions prior to undergoing standard treatment, formation of caseous necrotic briquettes encapsulated by fibers; ii) tuberculous pleurisy is encapsulated through pleural effusion absorption, which forms caseous spherical or briquette lesions encapsulated by fibrous tissues after further concentration; iii) mycobacterium tuberculosis reach pleura by hematogenous spread or lymphatic system spread, which forms tuberculous granulation and then caseous necrosis occurs, followed by limited fiber encapsulation; iv) caseous necrosis and liquidation occur in sub-pleural lymph gland and break into pleural cavity to cause pleurisy. Pleurisy absorbs left pleural adhesions; tuberculous lesions which originally occurred under pleura are encapsulated and condensed by fibrous connective tissues to form pleural tuberculosis; v) the early, sufficient and combined application of anti-tuberculosis drugs lowers human body's inflammatory reaction to pathogenic bacteria and the role of fibrinolytic enzyme, which results in effusive pleurisy concentration, drying and further forms tumors of pleural tuberculosis; and vi) non-timely and non-standard treatments to pleurisy and unreasonable use of hormones are important reasons for the formation of tumors of pleural tuberculosis.…”
Section: Discussionmentioning
confidence: 99%